Comparative Evaluation of Taper Preparation Variability of Three Different Niti Files- An In Vitro CBCT Study - Tirthankar Bhaumik; Utpal Kumar Das; Kaushik Dutta (European Scientific Journal, ESJ, 2017)
The ultimate goal of an endodontic treatment is to achieve the fluid tight seal particularly at the apex as well as in coronal aspect of the root canal system. This is mainly influenced by the cleaning and shaping of root canal system and it has been recognized as an important phase of endodontic therapy. Cleaning and shaping as well as obturation are best accomplished when the file taper claimed by the manufacturer is accurate and the taper of the canal following instrumentation corresponds to the taper of the file. Despite the most advanced technology in manufacturing of dental instruments, variations in endodontic file tapers still exist. Therefore the purpose of this study is to compare the taper variation in root canal preparations among the three different NiTi files using CBCT. Methods: 24 upper 1st molar tooth with mesiobuccal root curvature 15-30 degree were selected and divided into three groups. Mesiobuccal roots (MB1) of three groups were prepared by three different NiTi file system respectively up to size25 taper.06 and CBCT were done separately for each group. The diameter was measured at 1, 3, and orifice in mm and canal taper preparation was calculated using CBCT. Result: Of the 3 file systems, fell within the ±.05 taper variability. All preparations demonstrated variability when compared to the nominal taper .06. Conclusion: Taper preparations of the investigated size 25 taper .06 were favorable but different from the nominal taper.